Measurement of the banana pseudo-stem phenotypic parameters based on ellipse model - Jiang, Yinlong; Duan, Jieli; Xu, Xing; Ding, Yunhe; Li, Yang; Yang, Zhou (International Journal of Agricultural and Biological Engineering, 2022)
The measurement of banana pseudo-stem phenotypic parameters is a critical way to evaluate the growth status of bananas, and it can provide essential data support for mechanized cultivation operations such as fertilization and pesticide application. Existing studies mainly measure the diameter of banana pseudo-stem as its phenotypic parameter. The banana pseudo-stem cross section was closer to an ellipse other than a standard circle, so the diameter parameter cannot adequately represent the phenotypic characteristics of the banana plant. In this study, an automatic measuring device for banana pseudo-stem phenotypic parameters was developed. The device, which integrates three different types of sensors: a laser ranging sensor, a rotary encoder, and a digital camera, was used to obtain the point cloud and image data of banana pseudo-stem. A K-means point clouds clustering algorithm based on Euclidean distance was proposed. The point cloud of banana pseudo-stem was identified and extracted. A three-dimensional reconstruction algorithm based on the ellipse model was also proposed. The three-dimensional contour of the pseudo-stem was calculated to obtain three types of phenotypic parameters: the long axis length, the short axis length, and the perimeter. Further, a synchronous trigger image acquisition mechanism was used to take pictures of pseudo-stems during measurement. It can be utilized for manual assessment of the growth status of the banana. Field experimental results showed that the three banana phenotypic parameters had a high correlation with the manual measurement results, and R2 is always more significant than 0.95, the total average measurement error and relative error were only 6.16 mm and 4.38%, respectively, both are within the acceptable agronomy range. In general, this method has good universality for plant stem detection, and the stem phenotypic parameters can be obtained by means of a non-contact test, which is of great significance to the mechanized cultivation of the forest and fruit industry. Keywords: multi-sensor fusion, point cloud fitting, phenotypic parameter extraction, banana pseudo-stem, ellipse model DOI: 10.25165/j.ijabe.20221503.6614 Citation: Jiang Y L, Duan J L, Xu X, Ding Y H, Li Y, Yang Z. Measurement of the banana pseudo-stem phenotypic parameters based on ellipse model. Int J Agric & Biol Eng, 2022; 15(3): 195–202.